Kajian Penambahan Ragi Tape pada Pakan terhadap Konsumsi, Pertambahan Bobot Badan, Rasio Konversi Pakan, dan Mortalitas Tikus (Rattus norvegicus) - E M Sianturi; A M Fuah; K G Wiryawan (Faculty of Animal Science, Bogor Agricultural University, 2006)
An experiment was conducted to examine the effect of different levels of tape yeast addition into rations on Rattus norvegicus performance, such as feed consumption, body weight gain, feed conversion ratio and mortality. The experimental design used was a factorial completely randomized design 2 x 4, the first factor was sex (male and female rats), and the second factor was different levels of tape yeast added into rations (0% as R1, 0.5% as R2, 1% as R3 and 1.5% as R4). The results showed that the interaction between sex and yeast addition had significant effect on feed consumption and body weight gain (P < 0.05), but the effect was not significant on feed conversion ratio and mortality. Yeast addition in male-rat rations significantly reduced feed consumption, but did not affect body weight gain. In female rats, the addition of yeast in the rations increased body weight gain. Increasing levels of tape yeast in the rations improved the body weight gain and feed conversion ratio, especially for female rats (P < 0.05). There was no single rat died during the experimental period. Rats fed ration containing 1.5% yeast showed better feed consumption, weight gain, and feed conversion ratio compared to rats given other rations. Key words : rat, tape yeast, consumption, weight gain, feed conversion ratio, mortality